Gambaran karakteristik pasien in hospital cardiac arrest dan luaran pasca resusitasi jantung paru oleh tim code blue di RSUP Sanglah - Made Satria Yudha Dewangga; Hendy Wirawan; Anak Agung Ayu Dwi Adelia Yasmin (DiscoverSys Inc., 2022)
Background: Cardiac arrest is a medical emergency due to the sudden cessation of the heart’s mechanical function. Cardiac arrest can be reversible with appropriate intervention, but otherwise, it can be fatal and result in death. The incidence of cardiac arrest in hospital or in-hospital cardiac arrest (IHCA) needs to be considered because it is associated with high mortality and describes an early detection system and hospital response speed. In this study, the authors examined the characteristics of the incidence of IHCA and cardiopulmonary resuscitation carried out by the code blue team at the Sanglah Central General Hospital (RSUP), including outcome trends and survival of IHCA patients after cardiopulmonary resuscitation.Methods: The authors analyzed the incidence of IHCA at Sanglah Hospital in 2021 in a retrospective cohort by tracing the patient’s medical records from January to December 2021. The sample was collected using a non-randomized consecutive sampling technique, then univariate analysis was performed to get an overview of the proportion and percentage distribution, as well as analysis. Bivariate method to determine the relationship between age group, comorbidities, response time of the code blue team, and the etiology of cardiac arrest on resuscitation outcomes.Results: In IHCA patients who were resuscitated at Sanglah Hospital, 26.2% had a successful return of spontaneous circulation (ROSC), with >50% of patients dying within <24 hours and only 1% returning home recovering. The majority of IHCA patients were men aged 40 years or older, with a Charlson Comorbidity Index (CCI) 3, with noncardiac causes. Most resuscitation was performed within 5 minutes of the sound of the code blue signal. There was no significant relationship between age group, CCI score, etiology of cardiac arrest, and response time of the code blue team with resuscitation outcomes.Conclusion: IHCA patients at Sanglah Hospital have a relatively low survival rate, but the code blue efforts have been going well. There were no significant differences in the outcome of ROSC and death based on age group variables, comorbidities, response time of the code blue team, and the etiology of cardiac arrest. Latar Belakang: Henti jantung adalah keadaan darurat medis akibat berhentinya fungsi mekanis jantung secara tiba-tiba. Henti jantung dapat bersifat reversible dengan intervensi yang tepat, namun sebaliknya dapat bersifat fatal dan mengakibatkan kematian. Kejadian henti jantung di dalam rumah sakit atau in hospital cardiac arrest (IHCA) perlu diperhatikan karena berkaitan dengan mortalitas yang tinggi serta menggambarkan sistem deteksi dini dan kecepatan respon rumah sakit. Pada penelitian ini, penulis meneliti gambaran karakteristik kejadian IHCA dan resusitasi jantung paru yang dilakukan oleh tim code blue di Rumah Sakit Umum Pusat (RSUP) Sanglah, termasuk tren luaran dan kesintasan pasien IHCA pasca resusitasi jantung paru.Metode: Penulis menganalisis kejadian IHCA di RSUP Sanglah pada tahun 2021 secara kohort retrospektif melalui penelusuran rekam medis pasien dari bulan Januari hingga Desember 2021. Sampel dikumpulkan dengan teknik non randomized consecutive sampling, kemudian dilakukan analisis univariat untuk mendapat gambaran proporsi dan distribusi persentase, serta analisis bivariat untuk mengetahui hubungan antara kelompok usia, komorbid, waktu respon tim code blue, dan etiologi henti jantung terhadap luaran resusitasi.Hasil: Pada pasien yang IHCA yang diresusitasi di RSUP Sanglah, 26,2% yang berhasil mengalami return of spontaneous circulation (ROSC), dengan >50% pasien meninggal dalam waktu <24 jam dan hanya 1% yang pulang dalam kondisi sembuh. Mayoritas pasien IHCA adalah laki-laki usia 40 tahun atau lebih, dengan Charlson Comorbidity Index (CCI) ?3, dengan penyebab nonkardiak. Sebagian besar resusitasi sudah dilakukan dalam waktu 5 menit setelah dibunyikannya tanda code blue. Tidak terdapat hubungan yang signifikan antara kelompok usia, skor CCI, etiologi henti jantung, serta waktu respon tim code blue dengan luaran resusitasi.Simpulan: Pasien IHCA di RSUP Sanglah memiliki angka kesintasan yang relatif rendah, namun upaya code blue sudah berjalan dengan baik. Tidak ada perbedaan kejadian luaran ROSC maupun meninggal yang signifikan berdasarkan variabel kelompok usia, komorbid, waktu respon tim code blue, dan etiologi henti jantung.